2019
DOI: 10.1007/s13197-019-03577-0
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release of nisin from Neusilin particles to enhance food safety of sour curd cheese

Abstract: Nisin is frequently added as food additive to soft cheese to increase food safety against foodborne pathogens like Listeria monocytogenes. The goal of this study was the extension of the antimicrobial activity of nisin in sour curd cheese (SCC) by self-releasing adsorbed nisin from Neusilin UFL2 over production-based pH shift. First, the antimicrobial activity of nisin adsorbed to Neusilin UFL2 (UFL2-N) and free nisin was investigated in BHI broth at a pH range from 7.5 to 4.5 for each of six L. monocytogenes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Parent and adapted L. monocytogenes strains (inoculum: 2 × 10 8 cells mL −1 ) were incubated and gently shaken in 200 µL BHI without BC and in BHI supplemented with BC concentrations of 2, 3,4,5,6,8,9,10,11,12, and 13 µg mL −1 at 37 • C for 24 h. Colony forming units (CFUs) were determined in nine replicates according to the standard protocol of ISO 11290 [24].…”
Section: Determination Of Culturable Cells After Bc Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Parent and adapted L. monocytogenes strains (inoculum: 2 × 10 8 cells mL −1 ) were incubated and gently shaken in 200 µL BHI without BC and in BHI supplemented with BC concentrations of 2, 3,4,5,6,8,9,10,11,12, and 13 µg mL −1 at 37 • C for 24 h. Colony forming units (CFUs) were determined in nine replicates according to the standard protocol of ISO 11290 [24].…”
Section: Determination Of Culturable Cells After Bc Exposurementioning
confidence: 99%
“…The incubation period of listeriosis may be long (median 11 days, range 0-70 days) [1]. Listeria monocytogenes is usually transmitted by the consumption of contaminated food [2,3], and various foodstuffs have been identified as vehicles [2,[4][5][6]. Adverse conditions may induce tolerance or resistance towards environmental stress factors and/or a shift in L. monocytogenes from a culturable state to a viable but nonculturable state (VBNC) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Mature nisin is generated by posttranslationally modifying an immature precursor to produce a polypeptide with 34 amino acid residues containing one lanthionine, four methyl-lanthionine rings, and unusual residues such as dehydroalanine and dehydrobutyrine (Tong et al, 2010). Nisin has been granted a "generally regarded as safe" (GRAS) status and is approved for use as food preservative by the World Health Organization (WHO), the European Food Safety Authority (EFSA), and the United States Food and Drug Administration (FDA) (Szendy et al, 2019). Currently, it is widely used in dairy products and canned foods (Ahmad et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that nisin showed antibacterial activity to Gram-negative bacteria when subjected to specific circumstances, such as heat shock, osmotic shock, chelators (EDTA, citrates, lactoferrin, etc. ), and regulation of pH. , In recent years, a large number of bacteriocins with broad-spectrum antibacterial activity have been found, but the low yield of bacteriocins is one of the key problems of their wide application . There are several reports to improve the yield of bacteriocins including screening of LAB with high-yield bacteriocins, fermentation optimization, genetic engineering, etc. However, the regulatory mechanism of bacteriocin synthesis cannot be elucidated fundamentally and the improvement of bacteriocin yield is limited.…”
Section: Introductionmentioning
confidence: 99%
“…), and regulation of pH. 8,9 In recent years, a large number of bacteriocins with broad-spectrum antibacterial activity have been found, but the low yield of bacteriocins is one of the key problems of their wide application. 10 There are several reports to improve the yield of bacteriocins including screening of LAB with highyield bacteriocins, fermentation optimization, genetic engineering, etc.…”
Section: Introductionmentioning
confidence: 99%